2018
DOI: 10.1097/pec.0000000000001535
|View full text |Cite
|
Sign up to set email alerts
|

Resident Performance of the Rapid Cardiopulmonary Assessment in the Emergency Department

Abstract: Objectives The rapid cardiopulmonary assessment (RCPA) is an essential first step in effective resuscitation of critically ill children. Pediatric residents may not be achieving competency with resuscitative skills, including RCPA. Our objective was to determine how often pediatric residents complete the RCPA for actual patients. Methods This was an observational, cross-sectional study of senior residents (≥postgraduate year 2) performing the RCPA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These residents typically encounter fewer cases of cardiac arrest and consequently engage in less clinical practice, leading to a lower proficiency in CPR skills. Incorporating CPR as an assessment criterion can significantly enhance residents' emergency skills, ultimately contributing to the improved prognosis of critically ill children [18] .…”
Section: Table 3 Indicator Improvement Formentioning
confidence: 99%
“…These residents typically encounter fewer cases of cardiac arrest and consequently engage in less clinical practice, leading to a lower proficiency in CPR skills. Incorporating CPR as an assessment criterion can significantly enhance residents' emergency skills, ultimately contributing to the improved prognosis of critically ill children [18] .…”
Section: Table 3 Indicator Improvement Formentioning
confidence: 99%
“…At our institution, Sobolewski et al found that senior pediatric residents do not promptly nor thoroughly perform an initial RCPA on actual patients in the resuscitation area despite it being an expectation. 3 In this historical cohort, 6 (8.4%) of 71 senior residents assessed via video review completed any component of the perfusion exam and 7 (9.8%) of 71 verbalized their assessment of perfusion. 3 Experience and repetition of clinical assessments have been shown to improve exam skills; but pediatric residents have limited clinical opportunities to apply them in patients at risk for or in shock.…”
Section: Introductionmentioning
confidence: 99%
“…3 In this historical cohort, 6 (8.4%) of 71 senior residents assessed via video review completed any component of the perfusion exam and 7 (9.8%) of 71 verbalized their assessment of perfusion. 3 Experience and repetition of clinical assessments have been shown to improve exam skills; but pediatric residents have limited clinical opportunities to apply them in patients at risk for or in shock. 4,5 Educators have attempted to address this experience gap through high-fidelity simulation, which leads to increased skill retention compared with didactic training and lower-fidelity simulation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Observational studies have shown that senior residents in the pediatric emergency department (PED) have poor performance and limited exposure to rapid cardiopulmonary assessment of critically ill patients. 2 One survey of pediatric senior residents showed that only 22% had been the first responder to an actual patient resuscitation and 44% reported they had never led a resuscitation during residency. 3 Without this adequate experience, pediatric physicians may not feel comfortable appropriately caring for these patients after residency.…”
mentioning
confidence: 99%
“…In pediatrics, the “do one” aspect of this learning triad often becomes a rate-limiting step, especially when it comes to the resuscitation of critically ill patients, as pediatric medical and traumatic emergencies are less common than those in adult medicine 1 . Observational studies have shown that senior residents in the pediatric emergency department (PED) have poor performance and limited exposure to rapid cardiopulmonary assessment of critically ill patients 2 . One survey of pediatric senior residents showed that only 22% had been the first responder to an actual patient resuscitation and 44% reported they had never led a resuscitation during residency 3 .…”
mentioning
confidence: 99%